ALLERJİK VE ALLERJİK OLMAYAN BRONŞ ASTMASINDA LENFOSİT ALTGRUPLARI VE AKTİVASYON BELİRLEYİCİLERİ - GEMİCİOĞLU, Bilun and YILDIRIM, Nurhayat and GÜREL, Nuray and ADIN, Suzan and BADUR, Selim (Cerrahpaşa Medical Journal, 2014)
Background and Design. Peripheral blood lymphocyte subgroups and activation markers in bronchial asthma are studied mainly in cases with allergic or mixed etiology. This study investigates peripheral lymphocyte subgroups and activation markers in allergic and non allergic asthma cases and compares the results with suitable controls. Results. The study population consisted of 16 patients with allergic (A) asthma (10 women, 6 men with a mean age of 32.4 ± 9.1 SD years); 14 cases with non allergic (NA) asthma / 10 women and 4 men with a mean age of 33.2 ± 7.8 SD years) and 11 healthy (H) controls (5 women and 6 men with a mean age of 32.9 ± 8.9 SD years). CD3 and CD4 were found to be increased in all (A and NA) asthma patients (p<0.01) whereas CD19 and CD40 were found to be elevated only in A group (p<0.01). In NA group there was an increase in CD45 RO and a decrease in HLA DR. Conclusion. Total T lymphocytes and helper T lymphocytes are increased in all asthma patients. Allergic asthma patients have elevated B lymphocyte markers (CD19, CD40); non allergic asthma patients have increased memory T lymphocytes.